กรอบข่าวของสถานีโทรทัศน์เฉพาะแห่ง 3 สถานี ในช่วงความขัดแย้งทางการเมืองในประเทศไทย ระหว่าง วันที่ 2 มีนาคม ถึง 2 เมษายน พ.ศ. 2549 - ก้องเกียรติ สิริกาญจนาวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This qualitative research aims to study the news frames and content, the pictures in news and the voices presented to the audience of each television station and to learn about the rules and regulations as well as the culture of news production of each station during the political conflict from March 2nd to April 2nd 2006. It is found that during this period there were 3 stations presenting this issue and there were three kinds of news frames presented. These were 1) good news frame presented by ITV, 2) pro-government frame presented by Channel 11 and 3). non-biased frame presented by Channels 5